Complete mitochondrial genome sequence of Afla-Guard®, commercially available non-toxigenic Aspergillus flavus. Issue 3 (2nd July 2020) - Park, Jongsun; Lee, Mi-Kyung; Yu, Jae-Hyuk; Kim, Jong-Hwa; Han, Kap-Hoon
Abstract: Afla-Guard ® is a commercial non-toxigenic Aspergillus flavus strain used to decrease aflatoxin contamination level in field. Its mitochondrial genome was sequenced, showing that its length is 29, 208 bp with typical configuration of Aspergillus mitochondrial genome. 17 SNPs and 27 INDELs were identified by comparing with previous A. flavus mitochondrial genome. Phylogenetic trees present that A. flavus of Afla-Guard ® was clustered with the previous A. flavus mitochondrial genome.